ANALISIS KEEFEKTIFAN PEMBELAJARAN SOSIOLOGI MELALUI GOOGLE CLASSROOM KELAS XI IIS 2 SMAN 5 PONTIANAK - Desi Ratnasari; Rustiyarso Rustiyarso; Stella Prancisca (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the effectiveness of online sociology learning through google classroom during the Covid-19 pandemic Class XI IIS 2 SMA Negeri 5 Pontianak. The sub-problem in this study is how the teacher's efforts to increase the effectiveness of online sociology learning through google classroom and how the results of online sociology learning through google classroom during the Covid-19 pandemic Class XI IIS 2 SMA Negeri 5 Pontianak. The research method used is a descriptive method with a qualitative research form. Data collection techniques used were observation, interview, documentation. While the data collection tools used were observation guides, interview guides, and documentation. The analysis in this study is presented in a qualitative descriptive manner using 4 informants, namely sociology teachers and students of Class XI IIS 2 SMA Negeri 5 Pontianak. The results of this study prove the effectiveness of online sociology learning through google classroom and the teacher's efforts to improve online learning, then describe students who are learning through google classroom, with guidance from the teacher and the teacher instructs students to take attendance in google classroom, the teacher provides sociology subject matter that discussed online then students answer in the comments column after the discussion ends the teacher gives assignments so that students continue to study at home. From the results of the discussion of sociology lessons and the timely execution of assignments, the teacher can then assess the student.Keywords: Effectiveness, Sociology Learning, Google Classroom.